SICUREZZA ALIMENTARE IN EUROPA E LEGGE N. 283/1962: NORMA NAZIONALE ANCORA VIGENTE O ABROGAZIONE INDIRETTA? (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The authors analyze the process of interaction and the consistency of the Community law with the national law still in force on food safety, with reference to food crimes and focusing in particular on the toxic fraud.